Relevansi Pemikiran Politik Al-Ghazali Pada Sistem Politik Kontemporer - Muhammad, Rasyidin; Nura, Azillatul (Constitutional Law and Siyasah Department, Sharia and Law Faculty, IAIN, 2023)
The article aims to analyze the relevance of Al-Ghazali's political thought within the framework of contemporary political systems. To achieve this objective, the research focuses on identifying elements of Al-Ghazali's thought that can still contribute positively to the understanding and implementation of current political systems. Understanding why Al-Ghazali's thought remains relevant serves as the primary foundation for this study. This research adopts a library research methodology or approach, employing a philosophical perspective. This approach concentrates on gaining a profound understanding of Al-Ghazali's views on politics and assessing their relevance to contemporary political systems. The findings of this study suggest that Al-Ghazali's political thought, despite originating from a different historical context, retains significant relevance in contemporary political systems. The concepts of justice, integrity, and political ethics he proposed remain pertinent in addressing the challenges and dynamics of today's politics. However, to effectively apply these principles, adaptation and contextualization may be necessary to ensure they align with the complexities of modern political realities.